Uterine Transplantation: Advances, Challenges, and Future Perspectives - Ana Pereira; Flávia Ribeiro; Sandra Soares; Hélder Ferreira (Diseases)
Background: Infertility is a multifactorial condition with medical, psychological, demographic, and economic impacts. Around 3–5% of cases are due to uterine dysfunction. Absolute uterine factor infertility (AUFI) refers to infertility caused entirely by the absence or abnormality of the uterus, which prevents embryo implantation or pregnancy viability. Uterus transplantation (UTx) has emerged as a promising treatment for AUFI and has been successfully performed in over 10 countries. Objectives: This study aims to conduct a systematic review of uterus transplantation, evaluating its efficacy and safety, as well as maternal, neonatal, and long-term outcomes. It also explores current challenges and future directions. Methods: The methodology was registered on the PROSPERO platform. A literature search was performed in January 2025 across PubMed, Web of Science, and Scopus for articles published from January 2002 to December 2024 in English or Portuguese. The query was: “uterus/transplantation AND (pregnancy OR complications OR newborn OR premature OR diseases)”. Study quality was assessed by journal impact factor (IF). Data were analyzed using Microsoft Excel. Results: A total of 10 studies were included: four from Sweden, three from the DUETS group, two from the Czech Republic, and one multi-institutional American study. The UTx success rate was 74.0%; clinical pregnancy rate (CPR) and live birth rates (LBR) per embryo transfer (ET) were 36.3% and 22.0%, respectively. No significant increase in congenital or neurological complications was observed. Adverse psychological outcomes were associated with transplant failure or pregnancy loss. Conclusions: UTx is a promising treatment for AUFI, showing favorable pregnancy and birth outcomes without major fetal or neonatal risks.